GAPH Survey Forms 389-398 February 1981 - Smith, Bartholemew (South Georgia Area Planning and Development Commission, 1981)
1. 202 S. Seymore St., Quitman, Georgia 2. 512 E. Stephens St., Quitman, Georgia 3. 702 E. Stephens St., Quitman, Georgia 4. First Presbyterian Church 105 W. Stephens St., Quitman, Georgia 5. 209 W. Stephens St. Quitman, Georgia 6. 407 W. Stephens St. Quitman, Georgia 7. First Baptist Church Kindergarten, 509 W. Stephens St., Quitman, Georgia 8. 601 W. Stephens St., Quitman, Georgia 9. 607; 611 E. Steward St. and 605 S. Girard St., Quitman, Georgia 10. 403 E. Swamp St., Quitman, Georgia
Keywords: Lowndes County Historical Society (Lowndes County, Ga.); Real Property Surveys; Brooks County (Ga.); Quitman (Ga.); Historic Buildings